2019
DOI: 10.3847/1538-4357/ab2a01
|View full text |Cite
|
Sign up to set email alerts
|

Actinide-rich and Actinide-poor r-process-enhanced Metal-poor Stars Do Not Require Separate r-process Progenitors

Abstract: The astrophysical production site of the heaviest elements in the universe remains a mystery. Incorporating heavy element signatures of metal-poor, r -process enhanced stars into theoretical studies of r -process production can offer crucial constraints on the origin of heavy elements. In this study, we introduce and apply the "Actinide-Dilution with Matching" model to a variety of stellar groups ranging from actinide-deficient to actinide-enhanced to empirically characterize r -process ejecta mass as a functi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 96 publications
2
54
0
Order By: Relevance
“…Future data releases by the RPA will continue to increase the number of stars with identified r-process signatures and perhaps reveal new ones for investigations of the various proposed nucleosynthetic sites. Fresh investigations of actinide production, for example, are being used to distinguish between specific r-process sites and the conditions that produce these heavy elements (Eichler et al 2019;Holmbeck et al 2019a). Furthermore, the identification of dynamical groups that include r-process-enhanced stars are useful to constrain theoretical models of r-process production; see, e.g., Holmbeck et al (2019b) Opticon; Strasbourg Observatory; and the Universities of Groningen, Heidelberg and Sydney.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Future data releases by the RPA will continue to increase the number of stars with identified r-process signatures and perhaps reveal new ones for investigations of the various proposed nucleosynthetic sites. Fresh investigations of actinide production, for example, are being used to distinguish between specific r-process sites and the conditions that produce these heavy elements (Eichler et al 2019;Holmbeck et al 2019a). Furthermore, the identification of dynamical groups that include r-process-enhanced stars are useful to constrain theoretical models of r-process production; see, e.g., Holmbeck et al (2019b) Opticon; Strasbourg Observatory; and the Universities of Groningen, Heidelberg and Sydney.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…To do so, we employed an iterative random sampling procedure (see also Ref. [30]). In each iteration, we randomly selected ten trajectories, summed the abundances of 129 I and 247 Cm, and calculated the integrated 129 I / 247 Cm abundance ratio.…”
Section: Supplementary Textmentioning
confidence: 99%
“…Similarly, Ref. [30] showed that dynamical ejecta overproduce the Th/Eu elemental ratio derived from the surface of actinide-boost stars, which suggests that very neutron-rich conditions cannot entirely be responsible for the enrichment of these stars. Although current merger simulations tend to predict the presence of very neutron-rich material, these simulations still an active area of research, such that the dominance of very neutron-rich conditions in dynamical ejecta remains debatable.…”
mentioning
confidence: 98%
“…We note, however, that such ratios cannot be reliably used for actinide-boost r-process stars (Schatz et al 2002), which are known to exhibit unusually high Th and U abundances as compared to stable elements, such as Eu. Interestingly, the actinide element ratio, Th/U (if measured simultaneously in a star), seems to remain a robust tool to determine the ages of actinide-boost r-process stars (Holmbeck et al 2019).…”
Section: Introductionmentioning
confidence: 99%